Characterisation of a thiamine diphosphate-dependent alpha-keto acid decarboxylase from Proteus mirabilis JN458. (1st October 2017) - Wang, Biying; Bai, Yajun; Fan, Taiping; Zheng, Xiaohui; Cai, Yujie
Highlights: A gene encoding alpha-keto acid decarboxylase from Proteus mirabilis JN458 was cloned, overexpressed and characterised. Optimum activity of the enzyme was at pH 6.0 and 40–50 °C. The enzyme could be used to improve the flavour of cheese. Abstract: Alpha-keto acid decarboxylases can convert keto acids to their corresponding aldehydes, which are often volatile aroma compounds. The gene encoding α-keto acid decarboxylase in Proteus mirabilis JN458 was cloned, and the enzyme overexpressed in Escherichia coli BL21 (DE3), purified in high yield, and characterised. The molecular weight is 62.291 kDa by MALDI-TOF MS, and optimum activity at pH 6.0 and 40–50 °C. The enzyme is a typical decarboxylase, dependent on thiamine diphosphate and Mg 2+ as cofactors. For the decarboxylation reaction, the enzyme displayed a broad substrate range. Kinetic parameters were determined using 4-methyl-2-oxopentanoic acid, phenyl pyruvate and 3-methyl-2-oxopentanoic acid as substrates. K m and k cat values for phenyl pyruvate were 0.62 mM and 77.38 s −1, respectively, and the k cat / K m value was 124.81 mM −1  s −1 . The enzyme properties suggest it may act effectively under cheese ripening conditions.